Simulation and computation of oscillation and stability of hammer-pontoon systems - Menh, Nguyen Cao; Dac, Nguyen Van; Khiem, Vu Tan; Nga, Hoang (Vietnam Journal of Mechanics, 2000)
Hammer pontoon systems are usually used for pile-driving of onshore construction. The systems are constantly acted upon by marine wave, wind and current and have to be fixed by moorings. In this paper, on the basis of software ALASKA the system is simulated as dynamics of multi-body systems. Its natural frequencies and mode shapes are computed in order to avoid resonant phenomena by the change of design parameters. The vibration displacement at any point of the system is calculated for estimation of technical stability of the system. The reaction forces at joints between bodies and its inertial forces are obtained for calculation of system strength of material. The ambient exciting loads are regarded as deterministic forces and as stochastic ones. In the latter case, the load is given as spectral density function and it is necessary to calculate probability characteristics of system responses. An example is investigated for illustration.